PERAN KARANG TARUNA DALAM MENINGKATKAN PENDAPATAN UMKM MELALUI APLIKASI GOBIZ DI DESA BANDASARI - Moch Dafha Ardya; Sri Nurhayati; Ansori Ansori (Comm-Edu (Community Education Journal), 2023)
Karang Taruna is a forum for teenagers to be able to empower the community in various fields including the economy, and of course every family in a community must have a way to generate a source of livelihood in the form of money. However, with the lack of understanding of optimizing technology from the community, there must be a role for Karang Taruna in this problem, one of which is by helping the promotion of trade products through the Gobiz application that is connected to the internet. The purpose of this study is to describe how the role of Karang Taruna in increasing MSME income through the Gobiz application. The theory used is the theory of empowerment and community education training. The research method used is a qualitative method with a descriptive approach. The data collection technique was through observation and interviews, with one respondent being a youth youth coach, one youth organization administrator and two MSME actors. The main reason for using this instrument is to observe the problems faced by MSME actors and also related to the role of Karang Taruna in increasing MSME income through the Gobiz application in Bandasari Village, Perum Parken Blok D. The conclusion of this research is the role played by the Youth Organization Management. in increasing MSME income through the Gobiz application